1996
DOI: 10.1099/0022-1317-77-2-265
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the initiation codon for protein synthesis in foot-and-mouth disease virus RNA

Abstract: Foot-and-mouth disease virus (FMDV) RNA utilizes two in-frame initiation codons to produce two precursor proteins with identical carboxy termini. The 5' untranslated region (5'UTR) directs the ribosome to internal sequences without the need for a cap structure as used in host mRNAs. The FMDV 5'UTR was cloned upstream of the reporter gene chloramphenicol acetyltransferase (CAT) in order to study the selection of initiation site and to facilitate quantification of the translation products. After in vitro transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Addition of intact eIF2 resulted in a slight stimulation in overall translation as expected (Fig. 10B) and a significant increase in translation (34%, p Ͻ 0.006) from the upstream AUG which was evidenced by the increase in the ratio of preCAT:CAT (lane f); also in good agreement with previous studies (23). In contrast, addition of caspase 3-treated eIF2 did not stimulate translation in general or specifically increase translation from the upstream AUG (lane e).…”
Section: Figsupporting
confidence: 92%
See 1 more Smart Citation
“…Addition of intact eIF2 resulted in a slight stimulation in overall translation as expected (Fig. 10B) and a significant increase in translation (34%, p Ͻ 0.006) from the upstream AUG which was evidenced by the increase in the ratio of preCAT:CAT (lane f); also in good agreement with previous studies (23). In contrast, addition of caspase 3-treated eIF2 did not stimulate translation in general or specifically increase translation from the upstream AUG (lane e).…”
Section: Figsupporting
confidence: 92%
“…The selection of the initiation codon in mRNAs containing the FMDV 5Ј-UTR has been shown to be influenced by the activity of eIF2 and the amount of ternary complex eIF2⅐Met-tRNA⅐GTP (23,28) in a mechanism that may involve direct binding of eIF2 to the viral IRES RNA element (29). In previous studies, it was shown that the addition of eIF2 to in vitro translation lysates programmed with reporter mRNAs containing the FMDV 5Ј-UTR resulted in an increase in initiation from the upstream AUG (23).…”
Section: Figmentioning
confidence: 99%
“…Shortly afterwards, the requirements for different eIFs were investigated, revealing that eIF2 was necessary for EMCV mRNA translation [7]. Since then, all experiments with picornavirus mRNAs have provided overwhelming evidence for requirement of eIF2 for the initiation of picornavirus protein synthesis in cell free systems and in culture cells transfected with these mRNAs [8], [9], [10]. The elegant experiments by Pestova et al .…”
Section: Introductionmentioning
confidence: 99%
“…The T 7 TS-HRV/ EMCV/FMDV-CAT plasmids were constructed by inserting the 5 ′ UTR-CAT sequences as Eco RV-Bam HI fragments into a blunt-ended Hin dIII/ Bgl II-digested T 7 TS plasmid. The HRV fragment contained the 3 ′ 592 bp of the 5 ′ UTR (32), the EMCV 5 ′ UTR was a 3 ′ 607-bp fragment (22), and the FMDV 5 ′ UTR was a 530-bp fragment described earlier (39). The PV-CAT sequence (26) was inserted as a Hin dIII-Bam HI fragment into the Hin dIII/ Bgl II-digested T 7 TS, resulting in T 7 TS-PV-CAT.…”
Section: Construction Of the Plasmidsmentioning
confidence: 99%